Akupresure Meningkatkan Nafsu Makan Upaya Pengentasan Stunting Balita 13 – 59 Bulan - Sari, Kartika; Siti Haryani; Ana Puji Astuti (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2024)
The toddler years are a period of basic growth which influences subsequent development, including development in language, creativity, social and emotional intelligence. Malnutrition problems can affect brain development which ultimately causes a decline in the quality of human resources. (Nurwijayanti, 2017). Eating problems in children can also be overcome by non-pharmacological methods, including herbal medicine or herbal drinks, massage, acupuncture and acupressure. Acupressure is carried out by pressing using fingers or a blunt object on the body's meridian points or energy flow lines so that it is relatively easier and can be more specific for overcoming feeding difficulties in toddlers because it can improve blood circulation in the spleen and digestion (Widowati, 2022). The aim of this activity is to provide health education about stunting, a balanced diet and train mothers to do acupressure. The implementation of this PKM program is carried out using a participatory approach method. The results of this activity are that mothers understand more about the meaning, causes and characteristics of stunted children, how to prepare a balanced diet for stunted children and mothers are able to do acupressure to increase their children's appetite. The conclusion is that holding this PKM activity is very effective and useful in increasing the knowledge and understanding of young women about acupressure which is useful for increasing appetite as an effort to reduce stunting in toddlers 13 - 59 months.   ABSTRAK                 Masa balita menjadi masa pertumbuhan dasar yang berpengaruh terhadap perkembangan selanjutnya, di antaranya adalah perkembangan dalam berbahasa, berkreasi, bersosial dan kecerdasan emosional. Permasalahan gizi yang kurang terpenuhi dapat mempengaruhi perkembangan otak yang pada akhirnya menyebabkan penurunan kualitas sumber daya manusia. (Nurwijayanti, 2017). Masalah makan pada anak juga dapat diatasi dengan cara non farmakologi antara lain dengan jamu atau minuman herbal, pijat, akupunktur dan akupresur. Akupresur dilakukan dengan penekanan menggunakan jari atau benda tumpul pada titik meridian tubuh atau garis aliran energi sehingga relatif lebih mudah dan dapat lebih spesifik untuk mengatasi kesulitan makan pada balita karena dapat memperlancar peredaran darah pada limpa dan pencernaan (Wahyu, 2022). Tujuan kegiatan ini adalah untuk memberikan pendidikan kesehatan tentang stunting, menu makanan yang seimbang dan melatih ibu melakukan akupresure. Pelaksanaan program PKM ini dilaksanakan dengan metode pendekatan partisipatif . Adapun hasil dari kegiatan ini adalah ibu menjadi lebih paham tentang pengertian, penyebab dan ciri-ciri anak stunting, cara menyiapkan menu makanan yang seimbang untuk anak stunting serta ibu mampu untuk melakukan akupresure untuk meningkatkan nafsu makan pada anak-anak nya. Kesimpulan penyelenggaraan kegiatan PKM ini sangat efektif dan bermanfaat meningkatkan pengetahuan dan pemahaman remaja putri tentang akupresure bermanfaat untuk meningkatkan nafsu makan sebagai upaya pengentasan stunting balita 13 – 59 bulan.